2016
DOI: 10.1016/j.pmn.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain and Depressive Symptoms: Independent Predictors of Insomnia Symptoms among Adults with Sickle Cell Disease

Abstract: Background No studies to-date have systematically investigated insomnia symptoms among adults with sickle cell disease (SCD). The purpose of this study was to 1) describe the prevalence of insomnia symptoms and 2) identify bio-psychosocial predictors in community-dwelling adults with Sickle Cell Disease. Methods Cross-sectional analysis of baseline data from 263 African-American adults with SCD (aged 18 years or older). Measures included the Insomnia Severity Index (ISI), Center for Epidemiologic Studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…38 They also may have disturbed sleep or sleep-disordered breathing. [39][40][41][42][43][44] Fatigue may be severe, with severe anemia, and correlates substantially not only with pain but with sleep quality, anxiety, depression, and stress 45 and neurocognitive function and decreased quality of life. 46 Poor interpersonal relationships at work have been reported to be a larger contributor to unemployment than physical health in individuals with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…38 They also may have disturbed sleep or sleep-disordered breathing. [39][40][41][42][43][44] Fatigue may be severe, with severe anemia, and correlates substantially not only with pain but with sleep quality, anxiety, depression, and stress 45 and neurocognitive function and decreased quality of life. 46 Poor interpersonal relationships at work have been reported to be a larger contributor to unemployment than physical health in individuals with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…30 Pain and depression have also been shown to increase insomnia in adults with SCD in another study. 10 It is therefore plausible that the elimination of pain in an effective manner would ameliorate depressive symptomatology. We did observe that SCD patients with depression had a significantly greater number of days on analgesia/month compared with their non-depressed counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Among the few reports exploring psychiatric co-morbidity in adults with SCD, depression is commonly reported, with rates ranging between 2% and 57%. 612 Other studies have reported that anxiety disorders, 1315 alcohol abuse, psychosis, 4 suicidal ideation, 12 and sleep disturbances 16 are also common. Psychiatric co-morbidity in SCD is associated with increased hospital visits, 9 pain crises, 10 and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies had a maximum score 10,23,24 . And, two had scores equal to 11 25,26 . These two articles did not make clear the confounding factors and, consequently, the strategies to deal with them.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%